Silicon-tin-carbon composite material and preparation method and application thereof
By introducing porous carbon material and amorphous carbon cladding into the silicon tin material to form a double-layer core-shell structure, the problem of volume expansion of silicon tin material during charging and discharging is solved, and the electrochemical cycle stability and conductivity are improved.
Patent Information
- Application Number
- CN202411929344.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
The existing silicon tin materials are prone to volume expansion during charging and discharging, affecting the stability of electrochemical cycles.
A silicon-tin-carbon composite material composed of a porous silicon core, a porous carbon material cladding layer and an amorphous carbon coating layer is used to form a double-layer core-shell structure by embedding tin into the porous carbon material porous carbon material and covering it on the porous silicon.
By buffering the expansion and agglomeration of tin, the composite repairs the surface defects of porous silicon, inhibits volume expansion, improves the retention rate of circulation capacity, and enhances electrical conductivity.
Smart Images

Figure CN119650661A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-tin-carbon composite material and a preparation method and application thereof. Background Art
[0002] Silicon has an extremely high specific capacity (theoretically up to 4200 mAh / g, and actually up to 3600 mAh / g) and a low lithium storage potential, making it an ideal negative electrode material for new high-energy density batteries. However, silicon is a semiconductor and its conductivity is not as good as that of graphite, which severely limits its rate performance and low-temperature performance. The theoretical specific capacity of tin material can reach 993 mAh / g, and the lithium insertion / extraction potential of tin is much higher than the precipitation potential of Li. There is no need to worry about the problem of short circuit caused by the formation of lithium dendrites during the charge and discharge process, and therefore it exhibits higher safety performance. Tin has good conductivity and ductility. Compared with silicon, it is not easy to break during the lithium insertion and extraction process, and has fast charge and discharge capabilities and good low-temperature performance.
[0003] However, both silicon and tin materials are prone to volume expansion during the charging and discharging process, which reduces the stability of the material structure and affects the stability of the electrochemical cycle. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the existing silicon-tin material is prone to volume expansion during the charge and discharge process, which affects the electrochemical cycle stability, and to provide a silicon-tin-carbon composite material and a preparation method and application thereof. The silicon-tin-carbon composite material of the present invention has a good cycle capacity retention rate.
[0005] The present invention solves the above technical problems through the following technical solutions:
[0006] The present invention provides a silicon-tin-carbon composite material, which comprises, from the inside to the outside, a porous silicon core, a first coating layer and a second coating layer; the first coating layer comprises a porous carbon material and tin located in the pores of the porous carbon material, and the second coating layer comprises an amorphous carbon coating layer; the pores of the porous silicon core contain tin and the porous carbon material.
[0007] The present invention embeds tin into the pores of the porous carbon material and then composites it onto the porous silicon. Firstly, the porous carbon material has excellent conductivity, while ensuring the uniformity of the tin material in the porous silicon, preventing the tin material from melting and agglomerating, and improving the stability of the overall composite material.
[0008] In some embodiments, the porous carbon material in the pores of the porous silicon core further contains tin.
[0009] In some of the schemes, the tin content is 0.5-2%, such as 0.5%, 0.6%, 0.8%, 1% or 1.5%, where % refers to the mass fraction of tin in the silicon-tin-carbon composite material.
[0010] In some of the schemes, the carbon content is 5-15%, for example 5.5%, 6.4%, 7.2%, 10% or 12.5%, % refers to the mass fraction of carbon in the silicon-tin-carbon composite material; preferably, the carbon content of the porous carbon material is 2-10%, % refers to the mass fraction of porous carbon in the silicon-tin-carbon composite material; preferably, the content of amorphous carbon is 3-5%, % refers to the mass fraction of amorphous carbon in the silicon-tin-carbon composite material.
[0011] In some of the schemes, the silicon content is 83-94%, for example 87%, 89%, 92%, 93% or 94%, where % refers to the mass fraction of silicon in the silicon-tin-carbon composite material.
[0012] In some embodiments, the total thickness of the first cladding layer and the second cladding layer is 200 nm to 3 μm, for example, 500 nm, 700 nm, 800 nm, 1.2 μm or 1.8 μm.
[0013] In some embodiments, the porous carbon material is any one or more of graphene, carbon nanotubes and porous carbon.
[0014] In some of the embodiments, the D50 particle size of the graphene is 20-800 nm, for example, 200 nm or 400 nm.
[0015] In some embodiments, the diameter of the carbon nanotube is 2-20 nm, and the length of the carbon nanotube is preferably 1-50 μm.
[0016] In some embodiments, the D50 particle size of the porous carbon is 20-800 nm, for example, 500 nm.
[0017] In some embodiments, the porous carbon is hierarchical porous carbon, and the pore size of the hierarchical porous carbon is preferably 5-100 nm.
[0018] In some embodiments, the porosity of the porous carbon is greater than 90%, preferably 90-96%.
[0019] In some embodiments, the pore size of the porous silicon is 200 nm to 2 μm, for example, 700 μm, 800 nm, 1 μm, 1.2 μm or 1.5 μm.
[0020] In some of the embodiments, the porosity of the porous silicon is greater than 90%, preferably 92-96%, such as 93%, 94% or 95%.
[0021] The present invention also provides a method for preparing a silicon-tin-carbon composite material, which comprises the following steps:
[0022] (1) performing a first heat treatment on a mixture of tin powder and a porous carbon material to obtain a porous carbon composite material; the temperature of the first heat treatment is 240-500° C.;
[0023] (2) performing a second heat treatment on the mixture of the porous carbon composite material and porous silicon, so that the porous carbon composite material is coated on the porous silicon to obtain a preliminary coated material;
[0024] (3) An amorphous carbon layer is coated on the surface of the preliminary coating material to obtain a silicon-tin-carbon composite material.
[0025] In some of the schemes, the mass ratio of the tin powder to the porous carbon material is (1-10):100, for example, 5:100.
[0026] In some embodiments, the temperature of the first heat treatment is 240-300°C, for example, 250°C.
[0027] In some of the schemes, the holding time of the first heat treatment is 2 to 8 hours, for example 3 hours.
[0028] In some embodiments, the heating rate of the first heat treatment is 2-10°C / min, for example, 3°C / min.
[0029] In some embodiments, the first heat treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon.
[0030] In some of the schemes, the heating process of the first heat treatment also includes a stirring step, and the stirring speed is preferably 10-20 r / min, for example 15 r / min.
[0031] In some embodiments, a cooling step is further included after the first heat treatment is completed, and the cooling step preferably includes natural cooling to room temperature.
[0032] In some of the embodiments, the D50 particle size of the tin powder is 1-100 nm, for example, 10 nm, 20 nm, 40 nm, 60 nm or 80 nm.
[0033] In some embodiments, the porous carbon material is any one or more of graphene, carbon nanotubes and porous carbon.
[0034] In some of the schemes, the particle size of the graphene, the diameter and length of the carbon nanotubes, and the particle size, pore size and porosity of the porous carbon are the particle size of the graphene, the diameter and length of the carbon nanotubes, and the particle size, pore size and porosity of the porous carbon mentioned above.
[0035] In some of the embodiments, the mass ratio of the porous carbon composite material to the porous silicon is (1-10):100, for example, 1:100, 3:100, 5:100, 8:100 or 10:100.
[0036] In some embodiments, the temperature of the second heat treatment is 400-700°C, such as 500°C or 600°C.
[0037] In some of the schemes, the holding time of the second heat treatment is 2 to 7 hours, such as 4 hours, 5 hours or 6 hours.
[0038] In some embodiments, the heating rate of the second heat treatment is 3-10°C / min, for example, 2°C / min.
[0039] In some embodiments, the second heat treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon.
[0040] In some embodiments, a cooling step is further included after the second heat treatment is completed, and the cooling step preferably includes natural cooling to room temperature.
[0041] In some embodiments, the porous carbon composite material and the porous silicon are mixed in a mixer, and the mixer is conventional in the art, such as a plowshare mixer.
[0042] In some of the schemes, the method for preparing porous silicon includes: using silicon dioxide powder and magnesium powder as raw materials, and adopting magnesium thermal reduction method to prepare porous silicon.
[0043] In some of the schemes, the method for preparing the porous silicon includes: mixing silicon dioxide powder and magnesium powder and then performing a third heat treatment to obtain the porous silicon.
[0044] In some embodiments, the temperature of the third heat treatment is 500-900°C, such as 600°C or 650°C.
[0045] In some embodiments, the heating rate of the third heat treatment is 3-10° C. / min, for example, 5° C. / min.
[0046] In some of the schemes, the holding time of the third heat treatment is 2 to 10 hours, for example, 3 hours or 5 hours.
[0047] In some embodiments, the third heat treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon.
[0048] In some embodiments, the third heat treatment further includes the steps of grinding, washing and drying.
[0049] In some embodiments, the washing includes acid washing and water washing, and the acid washing preferably uses hydrochloric acid.
[0050] In some embodiments, the drying temperature is 80-110°C, for example, 100°C.
[0051] In some of the embodiments, the drying time is 14 to 20 hours, for example 16 hours.
[0052] In some of the schemes, the molar ratio of the magnesium powder to the silicon dioxide powder is (1-1.5):2, for example, 1.15:2 or 1.2:2.
[0053] In some of the embodiments, the D50 particle size of the silica powder is 5 to 50 μm, such as 25 μm, 30 μm, 40 μm or 50 μm.
[0054] In some of the embodiments, the D50 particle size of the magnesium powder is 5 to 100 μm, such as 10 μm, 20 μm, 30 μm, 35 μm or 50 μm.
[0055] In some embodiments, the pore size of the porous silicon is 200 nm to 2 μm, for example, 700 μm, 800 nm, 1 μm, 1.2 μm or 1.5 μm.
[0056] In some of the embodiments, the porosity of the porous silicon is 92-96%, such as 93%, 94% or 95%.
[0057] In some of the schemes, step (3) includes the following steps: mixing the preliminary coating material with a carbon source and then carbonizing it.
[0058] In some embodiments, the temperature of the carbonization treatment is 700-1100°C, such as 900°C or 1000°C.
[0059] In some of the schemes, the heating rate of the carbonization treatment is 2-10°C / min, for example 3°C / min.
[0060] In some of the schemes, the holding time of the carbonization treatment is 5 to 10 hours, for example 6 hours.
[0061] In the present invention, the temperature increase of the first heat treatment, the temperature increase of the second heat treatment, the temperature increase of the third heat treatment and the temperature increase of the carbonization treatment all refer to heating from room temperature to the final temperature.
[0062] In some embodiments, the carbonization treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon.
[0063] In some of the embodiments, the carbon source is any one of asphalt, citric acid, glucose and phenolic resin.
[0064] In some of the schemes, the mass of the carbon source is 2-8% of the mass of the preliminary coating material, such as 3% or 5%.
[0065] The present invention also provides a silicon-tin-carbon composite material prepared by the preparation method of the above-mentioned silicon-tin-carbon composite material.
[0066] The present invention also provides an application of the aforementioned silicon-tin-carbon composite material as a negative electrode material in a lithium-ion battery.
[0067] The present invention also provides a pole piece, which comprises the aforementioned silicon-tin-carbon composite material.
[0068] The present invention also provides an electrochemical device, which comprises the above-mentioned pole piece.
[0069] The positive and progressive effects of the present invention are:
[0070] The tin of the silicon-tin-carbon composite material of the present invention is located in the pores of the porous carbon layer, which buffers the expansion problem of tin and the agglomeration problem of tin in the subsequent high-temperature carbonization process. At the same time, the porous composite layer formed by tin and the porous carbon material is composited to the surface and pores of the porous silicon core to repair the surface defects of the porous silicon and limit the expansion of silicon to a certain extent. The outermost coated carbon layer can, on the one hand, inhibit the volume expansion of silicon and tin during the charge and discharge process while increasing the conductivity of the composite material, and on the other hand, prevent the porous composite layer from being directly in contact with the electrolyte and being decomposed, so that the present invention has a good cycle capacity retention rate;
[0071] The preparation method of the invention adopts a simple mechanical mixing and heating method, has a simple process, and is easy to realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 Schematic diagram of the structure of the composite negative electrode material according to an embodiment of the present invention.
[0073] Description of Figure Numbers:
[0074] Porous silicon core 1
[0075] First coating layer 2
[0076] Porous Carbon 21
[0077] Tin 22
[0078] Second coating layer 3 DETAILED DESCRIPTION
[0079] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0080] Example 1
[0081] (1) Tin powder (D50 particle size: 20 nm) and graphene powder (D50 particle size: 200 nm) were added into a mixer at a mass ratio of 5:100 and mixed thoroughly. The mixed materials were then transferred into a pressure-resistant heating reaction vessel with a stirring function. The rotation speed was 15 r / min, and the temperature was increased to 250°C at a heating rate of 3°C / min and kept at this temperature for 3 h. Nitrogen was introduced during the heating and holding process, and stirring was continued during the whole process. The mixture was then cooled to obtain a tin-graphene composite material.
[0082] (2) Magnesium powder (D50 particle size of 50 μm) and silicon dioxide (D50 particle size of 40 μm) were uniformly mixed in a molar ratio of 1.2:2, and the mixed powder was placed in a tubular furnace and heated to 600°C at a heating rate of 5°C / min, and kept warm for 3 h. After cooling to room temperature, the mixed powder was taken out, and nitrogen was introduced as a protective gas during the whole process; the calcined powder was broken up and ground, and then pickled with hydrochloric acid and washed with deionized water, and then dried in a forced air drying oven at 100°C for 16 h to obtain porous silicon micropowder; the pore size of the porous silicon obtained was 1 μm, and the porosity was 94%.
[0083] The tin-graphene composite material and porous silicon powder were added to a coulter mixer at a mass ratio of 5:100 and mixed thoroughly for 120 minutes. The mixture was placed in a sintering furnace and heated from room temperature to 500°C at a rate of 2°C / min for 5 hours under nitrogen protection, and then naturally cooled to room temperature to obtain a calcined powder.
[0084] (3) The calcined powder was mixed with asphalt accounting for 3% of the mass of the calcined powder, and then added to a carbonization furnace. Under nitrogen gas protection, the temperature was raised from room temperature to 1000°C at a rate of 3°C / min and kept for 6 h. The mixture was naturally cooled to room temperature to obtain a carbon-coated tin-graphene-porous silicon composite negative electrode material.
[0085] like Figure 1 As shown, the composite negative electrode material prepared in this embodiment includes a porous silicon core 1, a first coating layer 2 and a second coating layer 3 from the inside to the outside, the first coating layer 2 is a porous carbon 21 and tin 22 located in the pores of the porous carbon 21, and the second coating layer 3 is an amorphous carbon coating layer.
[0086] The silicon content is 92%, the carbon content is 7.2%, the tin content is 0.8%, and the total thickness of the first cladding layer and the second cladding layer is 800 nm.
[0087] The contents of silicon, carbon and tin in each example were measured using an infrared carbon content meter LECO CS844, an X-ray photoelectron spectrometer Thermo ESCALAB 250XI and an X-ray fluorescence analyzer PANalytical Axios, and the coating layer thickness was measured using a JEM-2100Plus transmission electron microscope.
[0088] Example 2
[0089] (1) Add tin powder (D50 particle size of 10 nm) and carbon nanotube powder (tube diameter of 2-20 nm, length of 1-50 μm) into a mixer at a mass ratio of 5:100 and mix them thoroughly. Then transfer the mixed materials into a pressure-resistant heating reaction vessel with a stirring function. The rotation speed is 15 r / min, and the temperature is increased to 250°C at a heating rate of 3°C / min and kept at this temperature for 3 h. Nitrogen is introduced during the heating and holding process, and stirring is continued throughout the process. Then the temperature is reduced to obtain a tin-carbon nanotube composite material.
[0090] (2) Magnesium powder (D50 particle size: 20 μm) and silicon dioxide (D50 particle size: 30 μm) were uniformly mixed in a molar ratio of 1.15:2, and the mixed powder was placed in a tubular furnace and heated to 650°C at a heating rate of 5°C / min, and kept warm for 5 h. After cooling to room temperature, the mixed powder was taken out, and nitrogen was introduced as a protective gas during the whole process; the calcined powder was broken up and ground, and then pickled with hydrochloric acid and washed with deionized water, and then dried in a forced air drying oven at 100°C for 16 h to obtain porous silicon micropowder; the pore size of the porous silicon obtained was 800 nm and the porosity was 93%.
[0091] The tin-carbon nanotube composite material and porous silicon powder were added to a plow mixer at a mass ratio of 8:100 and mixed thoroughly for 120 minutes. The mixture was placed in a sintering furnace and heated from room temperature to 500°C at a rate of 2°C / min for 5 hours under nitrogen protection, and then naturally cooled to room temperature to obtain a calcined powder.
[0092] (3) The calcined powder was mixed with asphalt accounting for 5% of the mass of the calcined powder, and then added to a carbonization furnace. Under nitrogen gas protection, the temperature was raised from room temperature to 1000°C at a rate of 3°C / min and kept for 6 h. The mixture was naturally cooled to room temperature to obtain a carbon-coated tin-carbon nanotube-porous silicon composite negative electrode material.
[0093] like Figure 1 As shown, the composite negative electrode material prepared in this embodiment includes a porous silicon core 1, a first coating layer 2 and a second coating layer 3 from the inside to the outside, the first coating layer 2 is a porous carbon 21 and tin 22 located in the pores of the porous carbon 21, and the second coating layer 3 is an amorphous carbon coating layer.
[0094] The silicon content is 89%, the carbon content is 10%, the tin content is 1%, and the total thickness of the first cladding layer and the second cladding layer is 1.2 μm.
[0095] Example 3
[0096] (1) Tin powder (D50 particle size: 60 nm) and carbon nanotube powder (tube diameter: 2-20 nm, length: 1-50 μm) were added into a mixer at a mass ratio of 5:100 and mixed thoroughly. The mixed materials were then transferred into a pressure-resistant heating reaction vessel with a stirring function. The temperature was increased to 250°C at a heating rate of 3°C / min at a rotation speed of 15 r / min and kept at this temperature for 3 h. Nitrogen was introduced during the heating and holding process. Stirring was continued during the whole process. The mixture was then cooled to obtain a tin-carbon nanotube composite material.
[0097] (2) Magnesium powder (D50 particle size of 10 μm) and silicon dioxide (D50 particle size of 40 μm) were uniformly mixed in a molar ratio of 1.15:2, and the mixed powder was placed in a tubular furnace and heated to 600°C at a heating rate of 5°C / min, and kept warm for 5 h. After cooling to room temperature, the mixed powder was taken out, and nitrogen was introduced as a protective gas during the whole process; the calcined powder was broken up and ground, and then pickled with hydrochloric acid and washed with deionized water, and then dried in a forced air drying oven at 100°C for 16 h to obtain porous silicon micropowder; the pore size of the porous silicon obtained was 1.5 μm, and the porosity was 95%.
[0098] The tin-carbon nanotube composite material and porous silicon powder were added to the plough VC mixer at a mass ratio of 1:100 and mixed thoroughly for 120 minutes. The mixture was placed in a sintering furnace and heated from room temperature to 600°C at a rate of 2°C / min under nitrogen gas protection for 6 hours, and then naturally cooled to room temperature to obtain a calcined powder.
[0099] (3) The calcined powder was mixed with asphalt accounting for 3% of the mass of the calcined powder, and then added to a carbonization furnace. Under nitrogen gas protection, the temperature was raised from room temperature to 900°C at a rate of 3°C / min and kept for 6 h. The mixture was naturally cooled to room temperature to obtain a carbon-coated tin-carbon nanotube-porous silicon composite negative electrode material.
[0100] like Figure 1 As shown, the composite negative electrode material prepared in this embodiment includes a porous silicon core 1, a first coating layer 2 and a second coating layer 3 from the inside to the outside, the first coating layer 2 is a porous carbon 21 and tin 22 located in the pores of the porous carbon 21, and the second coating layer 3 is an amorphous carbon coating layer.
[0101] The silicon content is 94%, the carbon content is 5.5%, the tin content is 0.5%, and the total thickness of the first cladding layer and the second cladding layer is 500 nm.
[0102] Example 4
[0103] (1) Tin powder (D50 particle size: 80 nm) and porous carbon powder (D50 particle size: 500 nm, pore size: 5-100 nm, porosity: 95%) were added into a mixer at a mass ratio of 5:100 and mixed thoroughly. The mixed materials were then transferred into a pressure-resistant heating reaction vessel with a stirring function. The temperature was increased to 250°C at a heating rate of 3°C / min at a rotation speed of 15 r / min and kept at this temperature for 3 h. Nitrogen was introduced during the heating and holding process. Stirring was continued during the whole process. The mixture was then cooled to obtain a tin-porous carbon composite material.
[0104] (2) Magnesium powder (D50 particle size of 30 μm) and silicon dioxide (D50 particle size of 25 μm) were mixed uniformly at a molar ratio of 1.15:2, and the mixed powder was placed in a tube furnace and heated to 600°C at a heating rate of 5°C / min, kept at this temperature for 5 hours, and then taken out after cooling to room temperature. Nitrogen was introduced as a protective gas during the whole process; the calcined powder was broken up and ground, and then pickled with hydrochloric acid and washed with deionized water, and then dried in a forced air drying oven at 100°C for 16 hours to obtain porous silicon micropowder. The pore size of the porous silicon obtained was 1.2 μm, and the porosity was 94%.
[0105] The tin-porous carbon composite material and porous silicon powder were added to a ribbon mixer at a mass ratio of 10:100 and mixed thoroughly for 120 minutes. The mixture was placed in a sintering furnace and heated from room temperature to 600°C at a rate of 2°C / min under nitrogen gas protection for 4 hours, and then naturally cooled to room temperature to obtain a calcined powder.
[0106] (3) The calcined powder was mixed with asphalt accounting for 5% of the mass of the calcined powder, and then added to a carbonization furnace. Under nitrogen gas protection, the temperature was raised from room temperature to 900°C at a rate of 3°C / min and kept for 6 h. The mixture was naturally cooled to room temperature to obtain a carbon-coated tin-porous carbon-porous silicon composite negative electrode material.
[0107] like Figure 1 As shown, the composite negative electrode material prepared in this embodiment includes a porous silicon core 1, a first coating layer 2 and a second coating layer 3 from the inside to the outside, the first coating layer 2 is a porous carbon 21 and tin 22 located in the pores of the porous carbon 21, and the second coating layer 3 is an amorphous carbon coating layer.
[0108] The silicon content is 87%, the carbon content is 12.5%, the tin content is 1.5%, and the total thickness of the first cladding layer and the second cladding layer is 1.8 μm.
[0109] Example 5
[0110] (1) Tin powder (D50 particle size: 40 nm) and graphene powder (D50 particle size: 400 nm) were added into a mixer at a mass ratio of 5:100 and mixed thoroughly. The mixed materials were then transferred into a pressure-resistant heating reaction vessel with a stirring function. The rotation speed was 15 r / min, and the temperature was increased to 250°C at a heating rate of 3°C / min and kept at this temperature for 3 h. Nitrogen was introduced during the heating and holding process, and stirring was continued during the whole process. The mixture was then cooled to obtain a tin-graphene composite material.
[0111] (2) Magnesium powder (D50 particle size: 35 μm) and silicon dioxide (D50 particle size: 50 μm) were uniformly mixed in a molar ratio of 1.15:2, and the mixed powder was placed in a tubular furnace and heated to 600°C at a heating rate of 5°C / min, and kept at this temperature for 5 h. After cooling to room temperature, the mixed powder was taken out, and nitrogen was introduced as a protective gas during the whole process; the calcined powder was broken up and ground, and then pickled with hydrochloric acid and washed with deionized water, and then dried in a forced air drying oven at 150°C for 16 h to obtain porous silicon micropowder; the pore size of the porous silicon obtained was 700 μm, and the porosity was 93%.
[0112] The tin-graphene composite material and porous silicon powder were added to a ribbon mixer at a mass ratio of 3:100 and mixed thoroughly for 120 minutes. The mixture was placed in a sintering furnace and heated from room temperature to 600°C at a rate of 2°C / min for 4 hours under nitrogen protection, and then naturally cooled to room temperature to obtain a calcined powder.
[0113] (3) The calcined powder was mixed with asphalt accounting for 5% of the mass of the calcined powder, and then added to a carbonization furnace. Under nitrogen gas protection, the temperature was raised from room temperature to 1000°C at a rate of 3°C / min and kept for 6 h. The mixture was naturally cooled to room temperature to obtain a carbon-coated tin-graphene-porous silicon composite negative electrode material.
[0114] like Figure 1 As shown, the composite negative electrode material prepared in this embodiment includes a porous silicon core 1, a first coating layer 2 and a second coating layer 3 from the inside to the outside, the first coating layer 2 is a porous carbon 21 and tin 22 located in the pores of the porous carbon 21, and the second coating layer 3 is an amorphous carbon coating layer.
[0115] The silicon content is 93%, the carbon content is 6.4%, the tin content is 0.6%, and the total thickness of the first cladding layer and the second cladding layer is 700 nm.
[0116] Comparative Example 1
[0117] Magnesium powder (D50 particle size is 30μm) and silicon dioxide (D50 particle size is 25μm) are mixed evenly at a molar ratio of 1.2:2, and the mixed powder is placed in a tube furnace and heated to 600℃ at a heating rate of 5℃ / min, kept warm for 3h, and taken out after cooling to room temperature. Nitrogen is introduced as a protective gas during the whole process; the calcined powder is broken up and ground, and then pickled with hydrochloric acid and washed with deionized water, and then dried at 100℃ in a forced air drying oven for 16h to obtain porous silicon micropowder. The pore size of the porous silicon is 1.2μm and the porosity is 94%.
[0118] Effect Example
[0119] The composite materials obtained in the above examples and comparative examples are used to prepare electrodes and assemble into half-cells. The preparation method of the half-cell is as follows:
[0120] The composite negative electrode material prepared in the embodiment and the comparative example: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) was mixed evenly and applied on the copper foil, and the coated electrode was placed in a vacuum drying oven at 110°C for 12 hours. The half-cell was assembled in a Braun glove box protected by argon gas, the electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio of 1:1:1), the metal lithium sheet was the counter electrode, and the half-cell test was carried out in a blue battery test cabinet.
[0121] The test parameters are: charge and discharge voltage is 0.001V-2V, and the charge and discharge rate is 0.1C.
[0122] The test results are shown in Table 1.
[0123] Table 1 Electrochemical performance test results
[0124]
[0125] Analysis of test results: The capacity retention rate of the embodiment after charge and discharge cycles is higher than that of the comparative example, indicating that the double-layer core-shell structure of the composite material alleviates the volume expansion of silicon tin during the charge and discharge process to a certain extent, improves the capacity of the composite material, and ensures the cycle performance.
Claims
1. A silicon-tin-carbon composite material, characterized in that: It includes a porous silicon core, a first coating layer and a second coating layer from the inside to the outside; the first coating layer includes a porous carbon material and tin located in the pores of the porous carbon material, and the second coating layer includes an amorphous carbon coating layer; the pores of the porous silicon core contain tin and the porous carbon material.
2. The silicon-tin-carbon composite material according to claim 1, characterized in that The silicon-tin-carbon composite material meets one or more of the following conditions: (a) the porous carbon material in the pores of the porous silicon core further contains tin; (b) the tin content is 0.5-2%, such as 0.5%, 0.6%, 0.8%, 1% or 1.5%, where % refers to the mass fraction of tin in the silicon-tin-carbon composite material; (c) the carbon content is 5-15%, for example, 5.5%, 6.4%, 7.2%, 10% or 12.5%, % refers to the mass fraction of carbon in the silicon-tin-carbon composite material; wherein the carbon content of the porous carbon material is preferably 2-10%; the content of the amorphous carbon is preferably 3-5%; (d) the silicon content is 83-94%, for example 87%, 89%, 92%, 93% or 94%, where % refers to the mass fraction of silicon in the silicon-tin-carbon composite material; (e) the total thickness of the first coating layer and the second coating layer is 200 nm to 3 μm, for example, 500 nm, 700 nm, 800 nm, 1.2 μm or 1.8 μm; (f) the porous carbon material is any one or more of graphene, carbon nanotubes and porous carbon; The D50 particle size of the graphene is preferably 20-800 nm, for example 200 nm or 400 nm; The diameter of the carbon nanotube is preferably 2-20 nm, and the length of the carbon nanotube is preferably 1-50 μm; The D50 particle size of the porous carbon is preferably 20-800 nm, for example 500 nm; The porous carbon is preferably hierarchical porous carbon, and the pore size of the hierarchical porous carbon is preferably 5-100 nm; The porosity of the porous carbon is preferably greater than 90%, more preferably 90-96%; (g) the pore size of the porous silicon is 200 nm to 2 μm, for example, 700 μm, 800 nm, 1 μm, 1.2 μm or 1.5 μm; (h) The porosity of the porous silicon is greater than 90%, preferably 92-96%, such as 93%, 94% or 95%.
3. A method for preparing a silicon-tin-carbon composite material, characterized in that: It includes the following steps: (1) performing a first heat treatment on a mixture of tin powder and a porous carbon material to obtain a porous carbon composite material; the temperature of the first heat treatment is 240-500° C.; (2) performing a second heat treatment on the mixture of the porous carbon composite material and porous silicon, so that the porous carbon composite material is coated on the porous silicon to obtain a preliminary coated material; (3) An amorphous carbon layer is coated on the surface of the preliminary coating material to obtain a silicon-tin-carbon composite material.
4. The method for preparing the silicon-tin-carbon composite material according to claim 3, characterized in that: Step (1) satisfies one or more of the following conditions: (a) the mass ratio of the tin powder to the porous carbon material is (1-10):100, for example, 5:100; (b) the temperature of the first heat treatment is 240-300°C, for example 250°C; (c) the holding time of the first heat treatment is 2 to 8 hours, for example 3 hours; (d) the heating rate of the first heat treatment is 2-10°C / min, for example 3°C / min; (e) the first heat treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon; (f) the heating process of the first heat treatment further comprises a stirring step, wherein the stirring speed is preferably 10-20 r / min, for example 15 r / min; (g) after the first heat treatment is completed, a cooling step is further included, wherein the cooling step preferably includes natural cooling to room temperature; (h) the porous carbon material is any one or more of graphene, carbon nanotubes and porous carbon; the D50 particle size of the graphene is preferably 20-800 nm, for example, 200 nm or 400 nm; the diameter of the carbon nanotubes is preferably 2-20 nm, and the length of the carbon nanotubes is preferably 1-50 μm; the D50 particle size of the porous carbon is preferably 20-800 nm, for example, 500 nm; the porous carbon is preferably hierarchical porous carbon, and the pore size of the hierarchical porous carbon is preferably 5-100 nm; the porosity of the porous carbon is preferably >90%, more preferably 90-96%; (j) The D50 particle size of the tin powder is 1-100 nm, for example, 10 nm, 20 nm, 40 nm, 60 nm or 80 nm.
5. The method for preparing the silicon-tin-carbon composite material according to claim 3, characterized in that: Step (2) satisfies one or more of the following conditions: (a) the mass ratio of the porous carbon composite material to the porous silicon is (1-10):100, for example, 1:100, 3:100, 5:100, 8:100 or 10:100; (b) the temperature of the second heat treatment is 400-700°C, for example, 500°C or 600°C; (c) the holding time of the second heat treatment is 2 to 7 hours, for example 4 hours, 5 hours or 6 hours; (d) the heating rate of the second heat treatment is 3-10°C / min, for example 2°C / min; (e) the second heat treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon; (f) after the second heat treatment is completed, a cooling step is further included, wherein the cooling step preferably includes natural cooling to room temperature; (g) The method for preparing porous silicon comprises: using silicon dioxide powder and magnesium powder as raw materials and adopting magnesium thermal reduction method to prepare porous silicon; Preferably, the method for preparing the porous silicon comprises: mixing silicon dioxide powder and magnesium powder and performing a third heat treatment to obtain the porous silicon; More preferably, the temperature of the third heat treatment is 500-900° C., for example, 600° C. or 650° C.; More preferably, the heating rate of the third heat treatment is 3-10°C / min, for example 5°C / min; More preferably, the holding time of the third heat treatment is 2 to 10 hours, for example 3 hours or 5 hours; More preferably, the third heat treatment is performed in a protective gas, and the protective gas is preferably nitrogen or argon; More preferably, the third heat treatment further includes grinding, washing and drying steps. Further preferably, the washing includes acid washing and water washing, and the acid washing is preferably carried out with hydrochloric acid. Further preferably, the drying temperature is 80-110° C., for example, 100° C.; further preferably, the drying time is 14-20 hours, for example, 16 hours. Preferably, the molar ratio of the magnesium powder to the silicon dioxide powder is (1-1.5):2, for example, 1.15:2 or 1.2:2; Preferably, the D50 particle size of the silicon dioxide powder is 5 to 50 μm, for example, 25 μm, 30 μm, 40 μm or 50 μm; Preferably, the D50 particle size of the magnesium powder is 5-100 μm, for example, 10 μm, 20 μm, 30 μm, 35 μm or 50 μm; (g) the pore size of the porous silicon is 200 nm to 2 μm, for example, 700 μm, 800 nm, 1 μm, 1.2 μm or 1.5 μm; (h) The porosity of the porous silicon is greater than 90%, preferably 92-96%, such as 93%, 94% or 95%.
6. The method for preparing the silicon-tin-carbon composite material according to claim 3, characterized in that: Step (3) comprises the following steps: mixing the preliminary coating material with a carbon source and then carbonizing the mixture; Preferably, step (3) satisfies one or more of the following conditions: (a) The temperature of the carbonization treatment is 700-1100°C, for example 900°C or 1000°C; (b) the heating rate of the carbonization treatment is 2-10°C / min, for example 3°C / min; (c) the carbonization treatment is carried out for a holding time of 5 to 10 hours, for example 6 hours; (d) the carbonization treatment is carried out in a protective gas, and the protective gas is preferably nitrogen or argon; (e) the carbon source is any one of asphalt, citric acid, glucose and phenolic resin; (f) The mass of the carbon source is 2-8% of the mass of the preliminary coating material, such as 3% or 5%.
7. A silicon-tin-carbon composite material prepared by the method for preparing a silicon-tin-carbon composite material as claimed in any one of claims 3 to 6.
8. Use of the silicon-tin-carbon composite material as claimed in any one of claims 1, 2 and 7 as a negative electrode material in a lithium-ion battery.
9. A pole piece, characterized in that: It comprises the silicon-tin-carbon composite material as described in any one of claims 1, 2 and 7.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Cited By
Silicon-based composite negative electrode material for all-solid-state lithium battery and preparation method of silicon-based composite negative electrode material
CN121862733A
Silicon-based negative electrode sheet, preparation method thereof and solid-state battery
CN122511843A